Identifikasi dan Potensi Hasil Tangkapan Pukat Cincin (Purse Seine) pada Kapal Supala Sari di Perairan Kabupaten Buleleng - I Ketut Wija Negara; Dewa Ayu Angga Pebriani (Current Trends in Aquatic Science, 2019)
The sustainable potential of fish capturing in Buleleng sea waters is 14.243,3 tons/year which consist of large-pelagic, small-pelagic, demersal, and other reef fish. This research was conducted to identify the catch of purse seine in Buleleng Regency, then found out the potential of capture fisheries resources. The location of this research was carried out around the waters of Buleleng Regency. It also involved fishing base of fishing fleet which is located at Fishing Base (PPI) of Sangsit. This research was conducted from May to August 2018. Fish identification resulted from purse seine during purse seine fishing gears are 8 species, namely Auxis thazard, Decapterus macarellus, Rastrelliger kanagurta, Caranx sexfasciatus, Elagatis bipinnulata, Canthidermis maculata, Kyphosus cinerasces dan Acanthocybium solandri. The composition and potential of the catch obtained during the purse Purse Seine is the most dominant are Auxis thazard and Decapterus macarellus. The total catch of Auxis thazard is 5.943 and Decapterus macarellus are 4.741 kg. The potential for fishing in the region of Buleleng Regency by using Purse Seine fishing gear is very large with the number of 10.903 kg in 5 times of operation.